Efektifitas Eksekusi Obyek Hak Tanggungan Menurut Hukum Positif - Elyza.Z; Yuliana Risna Maengkom; Diana R.W. Napitupulu (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Article 6 of the Mortgage Rights Law stipulates that if the debtor is in default, the first holder of the Mortgage Rights has the right to sell the object of the Mortgage Rights on its own authority through a public auction and collect the debt from the proceeds of the sale based on Article 6 of the Mortgage Rights Law. In reality, there is uncertainty of legal protection to creditors holding Building Rights Title collateral on Management Rights land, which is evidenced by the difficulty of creditors to execute collateral objects when the debtor defaults. The challenge that arises lies in the implementation of execution, where the execution of collateral is not as easy as the executorial power contained in the deed of acknowledgement of debt, so that the position of the creditor juridically has the right to execute when the debtor is declared in default.Research method is a process, principles and procedures for solving problems encountered in conducting research, which is an effort to discover, develop and test the truth of knowledge, which is carried out using scientific methods. In conclusion, Hak Tanggungan is a security right regulated in Law Number 4 Year 1996 as a substitute for mortgage and creditverband, with objects including property rights, business use rights, and building use rights. The encumbrance process involves two stages: the making of a Deed of Granting Mortgage Rights (APHT) by a PPAT and registration at the Land Office, which then results in a Mortgage Rights Certificate with the same executorial power as a court decision with permanent legal force. Mortgage Rights have the principles of preference, droit de suite, speciality, publicity, and ease of execution. Execution can be carried out through public auction based on the executorial title in the certificate or sale under the hand with certain conditions, such as notification to related parties and announcement in the media. Mortgage rights are extinguished due to debt repayment, relinquishment of rights by the creditor, a court order, or the extinguishment of the secured land rights.